Synthesis and characterization of polysulfone/montmorillonite (PSF/MMT) mixed matrix membrane for gas separation - Oh , P.C. (2014)
In this paper, flat sheet polysulfone (PSF) membrane and polysulfone/montmorillonite (PSF/MMT) mixed matrix membranes with different MMT contents were prepared by dry-wet phase inversion method. N-methyl-2-pyrrolidone (NMP) and deionized water were used as a solvent and coagulant, respectively. The morphology and structure of membranes were analyzed by scanning electron microscope. Thermogravimetric analysis was also performed to examine the thermal decomposition of the synthesized membrane. Results showed that MMT had a good dispersion in the PSF matrix.